IMPACT OF COMMUNITY INTEREST IN PAYING ZAKAT VIA MOBILE BANKING BANK SYARIAH INDONESIA - Fajar Satriyawan Wahyudi; Khurun’in Zahro; Nurjanna Ladjin (Adisam Publisher, 2024)
The rapid development of technology has had an impact in all fields, one of which is the banking sector. Advances in information and communication technology are reflected in Bank Syariah Indonesia, which is developing their services by offering mobile banking services, but customers still lack knowledge in using them because many customers do not want to know about banking developments. Awareness of using mobile banking can be said to be a growing feeling in mobile banking users to carry out their obligations in accordance with what they already know and understand. Because online zakat has enormous potential for the community's economy, considering that the Indonesian people have the largest number of Muslims in the world. And it cannot be denied that Indonesian Muslims are also mobile banking users who are active in banking activities. The strategy used to attract people to pay zakat still uses a fairly simple strategy. The strategy used in marketing zakat products is through brochures, banners, advertisements, radio. As an appeal to make it easier for customers to distribute their zakat using several methods, namely through Bank Syariah Indonesia mobile, especially mobile banking.